2021
DOI: 10.1002/btpr.3145
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of regenerable magnetic nanoparticles for cellulase immobilization: Improvement of enzymatic activity and stability

Abstract: To obtain regenerable magnetic nanoparticles, triethoxy(3-isocyanatopropyl)silane and iminodiacetic acid (IZ) were used as the starting material and immobilized on Fe 3 O 4 nanoparticles. Copper ions (Cu 2+ ions) were loaded on the Fe-IZ nanoparticles and used for cellulase immobilization. The support was characterized by spectroscopic methods (FTIR, NMR) and thermogravimetric analysis, transmission electron microscopy, scanning electron microscope, X-ray diffraction, energy dispersive X-ray analysis, and vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…A suitable magnetic field is created by adding biomolecules or organic substances to these magnetic nanoparticles, and the separation of substances can be performed quickly and easily by using magnets. [42,51] For the isolation of curcumin, unlike other purification techniques, the use of magnetic nanoparticles was preferred considering the advantage of a simple and fast separation technique with the help of magnets. In the study, Fe 3 O 4 nanoparticles were synthesized and their structure was confirmed by characterization techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A suitable magnetic field is created by adding biomolecules or organic substances to these magnetic nanoparticles, and the separation of substances can be performed quickly and easily by using magnets. [42,51] For the isolation of curcumin, unlike other purification techniques, the use of magnetic nanoparticles was preferred considering the advantage of a simple and fast separation technique with the help of magnets. In the study, Fe 3 O 4 nanoparticles were synthesized and their structure was confirmed by characterization techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[38] The prepared magnetic nanoparticles have been widely used in bionanotechnology such as magnetic resonance imaging, bioseparation, diagnostic agents, tumor hyperthermia and biomolecule immobilization. [39][40][41][42][43][44][45][46][47][48][49][50][51] These magnetic nanoparticles have attracted the attention of researchers with their small size, low toxicity, superparamagnetism and most importantly their specific applications. [36,[51][52][53][54][55] In this study, curcumin, which is the miracle of nature, was obtained by purifying it quickly and easily with magnetic iron oxide nanoparticles (IONPs) without the use of expensive instruments.…”
mentioning
confidence: 99%
“…100 The enzyme's stability and reusability after immobilization will be significantly improved, and the heterogeneous form of the enzyme will be easily separated from the reaction mixture. 101 Lyase, as an enzyme, is certainly no exception.…”
Section: Lyase Immobilizationmentioning
confidence: 99%
“…Copper (Cu) based nanostructures have been found to have an impact on the stability, immobilization, and recovery of enzymes among a variety of investigated nanomaterials (12). Furthermore, the inclusion of Cu-based nanomaterials may have improved the CAZymes' (carbohydrate-active enzymes) functional activity, which raises the efficiency of cellulose degradation during the enzymatic hydrolysis reaction (13). Platinum-based nanocatalysts can boost watersplitting efficiency.…”
Section: Introductionmentioning
confidence: 99%